(untitled) (Economic and Political Thought, 2012)
The article aims at answering the question whether the economic crisis (of the 1970s and the first decade of the 21st century) has impact on the Muslims’ decisions to immigrate. In order to illustrate this issue, I assumed it was necessary to discuss some historical aspects of immigration to France, which in the 1940s and 50s was mainly a goal for the citizens of Italy, Spain and Portugal. The influx of Muslims to France dates back to 1962, when Algeria gained independence, and has continued until now. As demographers, sociologists and political science experts highlight, the economic crisis does not influence the immigration decisions of Muslims from the poor countries of the North Africa and the Middle East. The main factor stimulating immigration of Muslims is the economic development level in their countries of origin. It is true that the number of Muslim immigrants is slightly decreasing but it is due to the restrictive immigration policy adopted by the host countries, i.e. the increase in the deportation quotas or the so-called selective immigration. The economic crisis made the host countries’ societies show their antiimmigration attitudes. The anti-Muslim attitude of the most important French politicians is also important. The example can be the President of the National Front – Marine Le Pen, who states “the economic crisis (including the one in France) results from supporting Muslims”, and the former President of France – Nicolas Sarkozy – famous for his ‘iron hand rule policy’ and controversial opinions about Muslims. The article ends with a hypothesis that the immigration policy of France is mainly influenced by such factors as cultural identity maintenance, and integration and/or security policy rather than a strictly economic factor.